Threats may be negative promises (but warnings are more than negative tips). Issue 5 (3rd July 2016) - Wray, Helen; Wood, Jeffrey S.; Haigh, Matthew; Stewart, Andrew J.
ABSTRACT: In everyday situations conditional promises, threats, tips, and warnings are commonplace. Previous research has reported disruption to eye movements during reading when conditional promises are produced by someone who does not have control over the conditional outcome event, but no such disruption for the processing of conditional tips. In the present paper, we examine how readers process conditional threats and warnings. We compare one account which views conditional threats and warnings simply as promises and tips with negative outcomes, with an alternative account which highlights their broader pragmatic differences. In an eye-tracking experiment we find evidence suggesting that, in processing terms, while threats operate like negative promises, warnings are more than negative tips.